Sejarah Peradaban Islam Dinasti Safawi: Kontribusi Politik, Sosial, dan Budaya dalam Perspektif Lintas Peradaban Islam (Safawi, Utsmani, dan Mughal) - Saidah, Nur; Bin Zakaria, Abd Razak; Atikah, Farihatul (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2025)
The Safavid Dynasty was one of the major Islamic empires that shaped modern Iranian identity through the integration of political authority and Twelver Shi‘ite theology. The dynasty’s emergence marked a new chapter in Islamic history, transforming Persia into the intellectual, political, and cultural center of Shi‘ite Islam. This article aims to analyze the political, social, and cultural contributions of the Safavid Dynasty within a cross-civilizational context, particularly by comparing its historical dynamics with those of its contemporaries, the Ottoman and Mughal empires. Employing a historical–qualitative method structured through the IMRAD framework, this research examines both primary chronicles and secondary scholarship, including twenty-first-century studies. The findings indicate that the Safavid Dynasty established a strong theocratic system, reinforced economic and artistic networks, and left a profound legacy on the formation of Iran’s national identity and the broader Islamic.